NATIVE-CENTEREDNESS IN THE ENGLISH LANGUAGE TEACHING MATERIALS: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS ON INDONESIAN ELT TEXTBOOKS’ COVER - Purba, Hilarius Raditya Priambada (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This is a multimodal critical discourse analysis of three Indonesian English language teaching textbooks. The study focused on the representation of the visuals on the cover to describe English as an International Language paradigm in Indonesia. This study was a qualitative study where the data were presented in the form of a narrative story. The researcher also employed themes to answer the research questions. The result showed that the orientation of English language teaching in Indonesia was native-centeredness where correctness was the focus of the process. Meanwhile, the practice would not prepare the student to have cross-cultural communication where English was used as the Lingua Franca. The result was likely to be in accordance with the latest study on Indonesian teachers’ perspective of the EIL paradigm which showed reluctance.